The Interaction of Borrelia Outer Surface Proteins with Tick Salivary Proteins - Paktan, Aylin (Jihočeská univerzita, 2022)
The aim of this thesis was to investigate the interaction of the salivary gland protein, Salp15, in relation to the outer surface protein C, OspC, using in silico analysis, as well as trying to amplify Salp15 from different tick species found in same geographical areas and observing the growth of Borrelia in the midgut and salivary glands of these different tick species in vitro.
The Interaction of Borrelia Outer Surface Proteins with Tick Salivary Proteins
Keywords: Lyme disease; Borrelia; Ixodes; Dermacentor; Salivary glands; Midgut; Salp15; OspC; Lyme disease; Borrelia; Ixodes; Dermacentor; Salivary glands; Midgut; Salp15; OspC